2022
DOI: 10.1002/fsn3.3143
|View full text |Cite
|
Sign up to set email alerts
|

The biological effect of a beef‐derived Latilactobacillus sakei on beef steaks during chilled storage

Abstract: The aim of this study was to investigate the biological inhibiting effect of a beef‐derived Latilactobacillus sakei (RS‐25) on the spoilage of beef steaks in overwrapped packaging during the 12 days of storage at 4°C. Beef quality as well as microbial indicators were determined at different intervals during the storage after the inoculation of RS‐25 at the 6 log CFU/g, and the high‐throughput sequencing was applied to investigate the changes of microbial community structure during the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 62 publications
(101 reference statements)
2
8
1
Order By: Relevance
“…On the other hand, other studies found lower as well as higher Br. thermosphacta concentrations initially and during (MAP) storage after treatment of meat with starter culture bacteria [12,13,[27][28][29]66], which agrees with the present results of beef on day 14. As the latter effect was found only on day 14 of storage, the results should be treated with caution.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, other studies found lower as well as higher Br. thermosphacta concentrations initially and during (MAP) storage after treatment of meat with starter culture bacteria [12,13,[27][28][29]66], which agrees with the present results of beef on day 14. As the latter effect was found only on day 14 of storage, the results should be treated with caution.…”
Section: Discussionsupporting
confidence: 92%
“…The mainly missing effects of the starter culture bacteria species L. sakei and S. carnosus on the target bacteria species Br. thermosphacta on pork and chicken meat, also during MAP storage, agree on the hand with other studies that analyzed these effect using meat [12,13,[63][64][65][66]. On the other hand, other studies found lower as well as higher Br.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…S. cerevisiae and La. sakei are microorganisms that are approved as generally recognized as safe (GRAS), meaning that they are safe for widespread use [45,46]. S. cerevisiae is a representative yeast used in food fermentation such as for bread, beer, and wine.…”
Section: Discussionmentioning
confidence: 99%